"It looks like he cares, but he doesn`t.": athletes` experiences of "good" and "bad" care in women`s football - Lewis, C. J.; Sawiuk, R.; Grimes, S. M. (Sports Coaching Review, 2023)
Care research in coaching has repeatedly prioritised the voice of the carer rather than those of the cared-for. This article addresses this shortfall and examines notions of care through the eyes of female footballers. These voices are pertinent because football (soccer) in the United Kingdom (UK) has been labelled micro-political, cut-throat, competitive, and at times, uncaring. Further, women`s voices are often marginalised in sport and research. Noddings` theory of care was selected to interpret semi-structured interviews of eight athletes` experiences of care in women`s football. Findings suggest that athletes were exposed to superficial acts of care impede their learning and performance. There were also safeguarding concerns regarding the touching of athletes. Interview extracts did, however, describe the positive orchestration of supporting networks to reinforce a "climate of care". Recommendations are provided for coaches on how to develop caring coaching.